If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2n + 3) + -5 = -70 Reorder the terms: 5(3 + 2n) + -5 = -70 (3 * 5 + 2n * 5) + -5 = -70 (15 + 10n) + -5 = -70 Reorder the terms: 15 + -5 + 10n = -70 Combine like terms: 15 + -5 = 10 10 + 10n = -70 Solving 10 + 10n = -70 Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-10' to each side of the equation. 10 + -10 + 10n = -70 + -10 Combine like terms: 10 + -10 = 0 0 + 10n = -70 + -10 10n = -70 + -10 Combine like terms: -70 + -10 = -80 10n = -80 Divide each side by '10'. n = -8 Simplifying n = -8
| 17x*6x-4*3=10 | | 0=x^2-10x+24 | | 5(40x-260)-25(80-20x)=226 | | 13-5x+7x-19=37 | | -8n+2n=-8-7n | | 25+.10x=35+.5x | | -1(3x+-13)=37 | | 0=5(7-x)+12 | | k-8=4 | | 5x+8=7c-0 | | 1.5-(32.8)= | | 7x-3.2=5.7 | | 4-d=(-d-4) | | 9(x+4)=-5x+4 | | 5x-8+3x=18 | | 6=c-9 | | -6(1+2x)=6(2x+1)+2x | | 60-5x=135-10x | | 43m+10-26m=27 | | 4y+3=(3-y)2 | | 32+-4x=84 | | 2d+1=16-d | | -48+6x=60+10x | | 0=x^4-10x^2+24 | | a=16+a | | -7(4x-9)=-7 | | 5x*7x+7*3=8 | | (3-u)(3u+7)=0 | | 6x+18=-2x-62 | | 4(5x-10)=-40+20 | | 1.3x+2=1 | | 9x^2+11=24x |